Pablo Guadarrama González, Filosofia Politica: Umanesimo in America Latina (Altre Modernità, 2019)
Pablo Guadarrama González, Filosofia Politica: Umanesimo in America Latina(Napoli, Guida Editore, 2018, 214 pp. ISBN 886-866-337-6)di Dimitri Endrizzi